TEACHERS’ STRATEGY TO OVERCOMING STUDENTS’ DIFFICULTIES IN LEARNING ENGLISH AT SMA ISLAM SULTAN AGUNG 1 SEMARANG - Cahyaningdyas, Ardhia Lutfi; Ekaningsih, Nur; Nugroho, Kurniawan Yudhi; Maharani, Mega Mulianing (Universitas Muria Kudus, 2023)
There are four abilities that are crucial to master when studying English. As English teacher, you have to master affective strategies if you hope to succeed in the learning process. This researcher is aimed to describe the teachers strategies in teaching learning English for senior high school students. This study used descriptive qualitative method. English teachers at SMA Islam Sultan Agung 1 Semarang were used as the sample in interviews, which served as the data source. The result, the two teachers used almost the same strategy given to the students. The first teacher used brainstorming, game, movie, song, and translation strategies. The other teacher used brainstorming, game, realia, motivation, activities (see, hear, and analyze), short movie, and song strategies. Those strategies was applied by teachers to solve problems faced by students in learning English at SMA Islam Sultan Agung 1 Semarang. The use of all of the above strategies provides positive changes indicated by the students when the English learning process takes place.